Evaluation of the "source " rules as contained in section 9 of the South African Income Tax Act as relating to software in the context of the digital economy - Flynn, Byron (Department of Finance and Tax, 2016)
In recent decades, the rise of the digital economy has drastically changed the way the world does business. Business can now be conducted without regard to geographical boundaries and limitations and organisations have the ability to conduct business making use of mobile and sophisticated software in South Africa without having a significant physical presence in the country. In addition, the characterisation of income from new software-related arrangements may be difficult to determine in this new economy. In response to the above, there is a general move globally to align taxation with economic substance and value creation and there is an increased focus on source-based taxation. Consequently, this dissertation conducts an analysis of the relevance and appropriateness of South Africa's source rules pertaining to software arrangements as contained in section 9 of the Income Tax Act (ITA) and as espoused in the common law. It is submitted that there are four main income characterisations applicable to software arrangements (sales, service arrangements, leases and royalties arrangements) and that it is possible to apportion a software-related payment into these various components for tax purposes. It is only once this characterisation has been completed that the source rules applicable to the various components should be applied. In relation to this, it is submitted that with the exception of show-how as espoused in section 49A of the ITA, the concepts of a royalty and know-how are consistent in the OECD Model Tax Convention and the ITA. Specifically, in determining if a software payment constitutes a royalty, a distinction should be made between the copyrighted article and the copyright itself, unless the component of the payment attributable to one of the items is clearly insignificant. Only the component of the payment attributable to the use of a copyright would constitute a royalty for South African tax purposes.